Measurement, determinants and outcomes of maternal care satisfaction in Nigeria: a systematic review - Jane E Hirst; Robyn Norton; Margaret Peden; Edward Mullins; Beatrice Wuraola Ope; Tavleen Wasan (BMJ Public Health)
Introduction Maternal mortality rates are unacceptably high in Nigeria. Understanding women’s satisfaction with the maternity health system is fundamental, as perceived quality of care is a determinant of service utilisation and improved birth outcomes.Objectives This systematic review aims to explore patients’ satisfaction with maternal healthcare in Nigeria, examining the measurement, determinants, and outcomes of satisfaction.Design A systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines.Data sources Searches were conducted in Embase, Maternity and Infant Care, Global Health, Ovid, Africa Journals Online, Cochrane Central Register of Controlled Trials, MEDLINE, Web of Science, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Scopus and Google Scholar, alongside citation searches of relevant studies.Eligibility criteria Original studies assessing patient satisfaction with maternal health services in Nigeria were included. There were no restrictions on study design types. Studies were excluded if they did not clearly define how satisfaction was measured or did not focus on the maternal health service domains under review (ie, antenatal, delivery, and/or postnatal care).Data extraction and synthesis Key information relevant to this study was extracted into an Excel spreadsheet and narratively synthesised. The Quality Assessment for Diverse Studies tool was used to appraise the quality of the selected literature.Results Maternal care satisfaction (MCS) ratings are high in Nigeria, but this may either indicate genuine positive experiences or be influenced by measurement-related biases. Several factors determine women’s satisfaction with maternity services. Key factors influencing MCS in Nigeria are positive client-provider relationships, a favourable hospital environment with easy accessibility and affordable care costs. While our study demonstrated a correlation between MCS and socioeconomic and demographic factors, there is no complete consensus within the literature about this correlation. Furthermore, patient satisfaction was associated with women’s future health-seeking behaviour and willingness to recommend care to others.Conclusion Understanding the multifaceted nature of MCS determinants and outcomes can better equip us to provide the support and care that mothers need to thrive. The findings from this study can inform policy, improve health responsiveness and ensure that women are provided with satisfactory and patient-centred maternity care, hence leading to a decline in poor pregnancy outcomes in Nigeria. It also highlights the need for robust methodologies that accurately measure women’s experiences, which is essential for enhancing the quality of maternal health services.PROSPERO registration number A protocol was developed for this study and published on PROSPERO, the International Prospective Register of Systematic Reviews (CRD42023414771).